Edukasi Pertolongan Pertama pada Sinkope di MAN 1 Banyumas - Nadini Chairani Nadini; Rahmaya Nova Handayani; Tophan Heri Wibowo (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
The sudden and often temporary loss of consciousness known as syncope is caused by a reduced supply of blood and oxygen to the brain. Students at all levels of education, especially those whose schools hold Monday ceremonies, are at higher risk of syncope due to prolonged exposure to the sun. Careful provision of first aid to those who faint is necessary due to the potential for major complications. The aim of this PkM is to help the community know more about syncope and how to provide first aid. This PkM used learning strategies such as lectures and demonstrations. Thirty people attended and participated in this activity. On Wednesday, 12 June 2024, the event took place at MAN 1 Banyumas. Videos, brochures, and PowerPoint presentations. The results of Community Service on the level of knowledge before education were 9 participants (30.0%) had poor knowledge, 12 participants (40.0%) had sufficient knowledge, and 9 participants (30.0%) had good knowledge. Whereas after being given education, 27 participants (90.0%) were in the good category and 3 participants (10.0%) in the moderate category. The level of skills before being given education was 30 participants (100.0%), while after being given education as many as 30 participants (100.0%) had skilled skills. Based on the results of the presentation of pretest, posttest knowledge and skills that have been carried out, it shows an increase in knowledge and skills.